Bystanders in Mob Justice: Interrogating Public Complicity and Intervention in Bayelsa State, Nigeria - Inimiesi , Oba Preye (Academia Journal of Humanities & Social Sciences, 2026)
This study examines the role of bystanders during mob justice in Bayelsa State, Nigeria. Specifically, the study assessed the role of bystanders in mob justice incidents and how victims interpreted their actions or inactions. This objective is in consonance with the corresponding research question that guided the investigation. To achieve the objective of this study, a mixed-method approach was employed, using questionnaire and interview method as the research instruments. The sample size for the study was 400. The samples were selected using a multi-staged sampling technique (i.e., cluster, simple random, convenience and the snowball sampling technique respectively). In the course of the study, 336 questionnaires were retrieved, collated and analyzed. Two analytical techniques were adopted namely, the simple percentage and the thematic method. While, the first was used to evaluate the research questions and objectives, the second was opted to analyze the interview. The results from the data analysis revealed that the involvement of bystander in mob justice actions cannot be written off as incidental. Whether active or passive, their roles form a part of the trauma that the victim has experienced. Bystanders’ involvement in mob incidents is a reflection of the public’s disenchantment with the legal system, which leads to widespread cooperation in extrajudicial activities. The study recommends that the Bayelsa State government, in partnership with Non-governmental Organizations should integrate de-escalation and active bystander training into community programs. They should collaborate to offer practical training on de-escalation techniques and active bystander intervention.